ANALYSIS EFFECTIVENESS OF ADVERTISING ON WEB SERIES TO THE DECISION OF PURCHASING TROPICANA SLIM STEVIA (Study on Sore: Istri Dari Masa Depan Web Series) - Anisa Noor Fitriana; Sigit Tripambudi; Prayudi Prayudi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
Web Series includes new media to advertise, the effectiveness seen in this research is after viewers watch the Web Series